Commentary on From the War on Terror to the Moral Crusade Against Female Genital Mutilation - Abbas, Sarah Mohammedahmed (Violence against women, 2023)
This commentary reflects on Dina Bader's article From the War on Terror to the Moral Crusade Against Female Genital Mutilation, in which the author chronicles the rise in state laws prohibiting female genital mutilation/cutting (FGM/C) through a lens of femonationalism. Expanding upon Bader's thought-provoking article, this commentary adds additional reflection on the content of current state legislation and the need for more comprehensive laws to protect women and girls. Future legislation must be evidence-based and must be accompanied by a multisectoral approach to prevention and response in order to create an enabling environment for the elimination of FGM/C.